Antibacterial Study Of Olive-based Ferulate Esters - Nurul Jannah Abd Rahman; Salina Mat Radzi; Hanina Mohd Noor; Norlelawati Ariffin (World Journal of Pharmacy and Pharmaceutical Science, 2024)
Volume 4, Issue 1